In vivo evidence of hippocampal dentate gyrus expansion in multiple sclerosis. Issue 11 (19th August 2015) - Rocca, Maria A.; Longoni, Giulia; Pagani, Elisabetta; Boffa, Giacomo; Colombo, Bruno; Rodegher, Mariaemma; Martino, Gianvito; Falini, Andrea; Comi, Giancarlo; Filippi, Massimo
Abstract Using MR‐based radial mapping, we assessed morphological alterations of the hippocampal dentate gyrus (DG) in patients with relapse‐onset multiple sclerosis (MS). We analyzed different stages of the disease and the association of DG alterations with hippocampal‐related cognitive functions. Using high‐resolution morphological imaging, hippocampal radial mapping analysis was performed in 28 relapsing‐remitting (RR), 34 secondary progressive, and 26 benign MS patients and 28 healthy controls (HC). Between‐groups differences of DG radial distance (from surface points to the central core of the hippocampus) and correlations with clinical, neuropsychological, and radiological measures were evaluated using surface‐based mesh modeling. Compared with HC, all MS clinical phenotypes revealed a larger radial distance of the DG, which was more marked on the left side. Radial distance enlargement was more pronounced in RRMS patients compared with the other disease clinical phenotypes and was inversely correlated to disease duration. Radial distance enlargement was correlated with higher T2 lesion volume and a better cognitive performance in RRMS and with a poor cognitive performance in secondary progressive and benign MS patients. Surface expansion of the DG might represent an inflammation‐induced neurogenic (reactive) process of the subgranular zone of the hippocampus primarily aimed at rescuing the functional competence of hippocampal circuitry. Hum Brain Mapp 36:4702–4713, 2015. © 2015 Wiley Periodicals, Inc.